2020
DOI: 10.1016/j.pacfin.2020.101396
|View full text |Cite
|
Sign up to set email alerts
|

The Korea discount and chaebols

Abstract: Finance practitioners frequently claim that stocks of Korean firms are undervalued and trade at a discount relative to foreign firms. This phenomenon is commonly called "the Korea discount". It is based on anecdotal evidence comparing either the price-earnings ratios of different market indexes or those of different individual stocks. This paper provides empirical evidence on the existence of such a discount using a large sample of stocks from 28 countries over the period 2002-2016. We find that Korean stocks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…Following the International Monetary Fund's (IMF) bail out in 1997, Korean capital markets have experienced fundamental changes, including the accounting systems. Therefore, to be consistent with other Korean‐based studies (e.g., An, 2015; Dibooglu & Cevik, 2016; Ducret & Isakov, 2020; Kim et al., 2014; Pyo, 2021), we construct our sample with a starting date set from 2000. Panel A of Table 1 summarizes the PEs during the 2000–2018 period.…”
Section: Data and Research Designmentioning
confidence: 94%
See 3 more Smart Citations
“…Following the International Monetary Fund's (IMF) bail out in 1997, Korean capital markets have experienced fundamental changes, including the accounting systems. Therefore, to be consistent with other Korean‐based studies (e.g., An, 2015; Dibooglu & Cevik, 2016; Ducret & Isakov, 2020; Kim et al., 2014; Pyo, 2021), we construct our sample with a starting date set from 2000. Panel A of Table 1 summarizes the PEs during the 2000–2018 period.…”
Section: Data and Research Designmentioning
confidence: 94%
“…Furthermore, Korea's institutional environment is normally characterized as a low-quality legal system offering a weak investor protection (Ball et al, 2003(Ball et al, , 2010Bushman & Piotroski, 2006). Meanwhile, extant literature has shown that Korean government and ruling party' policy significantly affect firms' operations (e.g., Chiu et al, 2005;Ducret & Isakov, 2020;Kim, 2021;Song et al, 2014). For example, Chun et al (2023) document that Korean private firms are likely to increase the corporate donation when the incumbent government is progressive party rather than conservative party.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Examples of Chaebol include Samsung, Hyundai, SK and Lotte. These companies were the engines of growth behind Korea"s fast development throughout the 1970s and 1980s, and they continue to play a pivotal role in the economy (Ducret & Isakov, 2019). There is a strong connection between the national pride of Korea and the success of these companies, especially for older generations (Uttam, 2019).…”
Section: Politically Sensitive Job Sectorsmentioning
confidence: 99%